Self-esteem mediates the relationship between physical activity and smartphone addiction of Chinese college students: a cross-sectional study - Ke, Yuanyuan; Liu, Xiuxia; Xu, Xue; He, Bingchen; Wang, Jinfu; Zuo, Lijun; Wang, Haiyun; Yang, Guan (Frontiers in Psychology, 2024)
Smartphone addiction, as a key topic in the current field of behavioral addictions and public health, has brought many negative impacts on the physical, psychological, interpersonal communication, and even academic performance among contemporary college students. Therefore, the purpose of this study is to offer ideas for solving smartphone addiction among college students through investigating the potential mediating effect of self-esteem in the relationship between physical activity and smartphone addiction. Methods: By the quota sampling, a crosssectional study was conducted to investigate 650 college students from 10 colleges in Guangzhou Higher Mega Center, and several self-reported instruments including physical activity rating scale-3 (PARS-3), mobile phone addiction tendency scale (MPATS), self-esteem scale (SES) were used to collect the related data needed for the present study. The descriptive analysis, correlation analysis, hierarchical regression analysis, and mediating effect analysis in this study were performed in turn. Results: The results showed that physical activity (r=-0.124, p<0.01) and self-esteem (r=-0.360, p<0.01) were all negatively correlated with smartphone addiction, and both could also significantly and negatively predict smartphone addiction. There was a positive correlation between physical activity and self-esteem (r = 0.084, p<0.05), and self-esteem could be significantly predicted by physical activity. And more important, the relationship between physical activity and smartphone addiction could be partially mediated by self-esteem, and the indirect effect value was -0.346 (95% Boot CI = -0.695; -0.023), along with the mediating effect accounted for 24% of the total effect between physical activity and smartphone addiction. Conclusions: The current study shows that physical activity could not only directly reduce smartphone addiction, but also decrease smartphone addiction by indirectly improving self-esteem, which is important in practice for solving this troublesome issue and then gradually developing a healthy behavior in daily life for college students in China, and even across the world in near future.